2023
DOI: 10.7554/elife.86655
|View full text |Cite
|
Sign up to set email alerts
|

Molecular portraits of colorectal cancer morphological regions

Abstract: Heterogeneity of colorectal carcinoma (CRC) represents a major hurdle towards personalized medicine. Efforts based on whole tumor profiling demonstrated that the CRC molecular subtypes were associated with specific tumor morphological patterns representing tumor subregions. We hypothesize that whole-tumor molecular descriptors depend on the morphological heterogeneity with significant impact on current molecular predictors. We investigated intra-tumor heterogeneity by morphology-guided transcriptomics to bette… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Our group ( Popovici et al, 2017 ) and later others ( Sirinukunwattana et al, 2021 ) managed to replicate the transcriptome-based molecular classification of CRC using automatic analysis of readily available high-resolution digital haematoxylin-eosin (H&E) slides. These results confirmed the close relationship between tumor morphology and coding transcriptome and were further strengthen by our recent analysis of the molecular programs associated with specific morphological patterns ( Budinská et al, 2023 ).…”
Section: Introductionsupporting
confidence: 86%
See 4 more Smart Citations
“…Our group ( Popovici et al, 2017 ) and later others ( Sirinukunwattana et al, 2021 ) managed to replicate the transcriptome-based molecular classification of CRC using automatic analysis of readily available high-resolution digital haematoxylin-eosin (H&E) slides. These results confirmed the close relationship between tumor morphology and coding transcriptome and were further strengthen by our recent analysis of the molecular programs associated with specific morphological patterns ( Budinská et al, 2023 ).…”
Section: Introductionsupporting
confidence: 86%
“…However, even prior to the CMS, our research indicated that the CRC transcriptome subtypes are linked to various morphological patterns ( Budinská et al, 2013 ). Having those patterns as a starting point, we later identified pattern-specific molecular programs in CRC ( Budinská et al, 2023 ). Hence, we wanted to analyze the whole spectrum of morphological heterogeneity by using both expert pathologist and AI-based methodology and by considering four slides per tumor (from different FFPE blocks).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations